Discovery of conserved peptide-MHC epitopes for directly alloreactive CD8+ T cells - Hill, Alexandra E.; Son, Eric T.; Paul-Heng, Moumita; Wang, Chuanmin; Ratnaseelan, Shivanjali; Denkova, Martina; Faridi, Pouya; Braun, Asolina; Purcell, Anthony W.; Mifsud, Nicole A.; Sharland, Alexandra F. (Frontiers in Transplantation, 2025)
Mass Spectrometry allied with in-vivo generation of activated alloreactive T cell populations and tetramer screening facilitates the identification of endogenous peptides that are directly recognised in complex with allogeneic Major Histocompatibility class I (MHC I) molecules by alloreactive CD8+ T cells. We had previously used this approach for the discovery of immunogenic self-peptides presented by the allomorph H-2Kb (Kb). In this study, we identified 22 highly immunogenic self-peptides presented by H-2Kd (Kd). Peptide abundance across skin, spleen and liver samples (estimated as the product of the spectral intensity obtained for these samples) was the principal factor influencing recognition of peptide-Kd epitopes. Predicted binding affinity (BA score) and overall peptide hydrophobicity were also independently correlated with immunogenicity, while there was no significant correlation between the IEDB immunogenicity score and the proportion of T cells recognising a given epitope. Eight peptide-Kd epitopes were selected for inclusion in a tetramer panel to detect directly alloreactive CD8+ T cells. This panel bound over 30% of activated alloreactive CD8+ T cells after a prime-boost against Kd. Moreover, the panel identified alloreactive CD8+ T cells within the graft infiltrate, spleen and draining lymph node during rejection of a Kd-bearing heart graft. In conclusion, small animal studies have demonstrated the feasibility of high-throughput approaches for the discovery of pMHC epitopes recognised by directly alloreactive T cells. Translating this approach to the human setting is achievable and will yield both critical insights into the fundamental basis of alloreactivity and powerful tools for immune monitoring in transplantation.